2022
DOI: 10.1155/2022/9910841
|View full text |Cite|
|
Sign up to set email alerts
|

A Rehabilitation Model Conducive to Postoperative Recovery of Endometrial Cancer Patients after Laparoscopy

Abstract: Although collaborative care is increasingly being implemented in the treatment of various diseases, there are currently no related studies on its effects in endometrial cancer patients after laparoscopic treatment. Thus, this study is aimed at investigating the significance of an integrated medical and nursing care model for women with gynecologic malignant tumors who underwent laparoscopic treatment. The patients were randomly divided into a medical-nursing integrated nursing group (study group) and a general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It has been verifed in long-term practice that the application of emergency green channel greatly increases the rescue time of patients, prolongs their life cycle, and improves their prognosis and quality of life [4]. Based on this view, previous studies suggested that targeted psychological intervention combined with planned pain care could improve pain after AIO surgery [5]. Some studies also indicate that rapid rehabilitation nursing can promote postoperative recovery [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been verifed in long-term practice that the application of emergency green channel greatly increases the rescue time of patients, prolongs their life cycle, and improves their prognosis and quality of life [4]. Based on this view, previous studies suggested that targeted psychological intervention combined with planned pain care could improve pain after AIO surgery [5]. Some studies also indicate that rapid rehabilitation nursing can promote postoperative recovery [6].…”
Section: Introductionmentioning
confidence: 99%
“…is may be attributed to the rapid rehabilitation of the gastrointestinal function of patients undergoing rapid rehabilitation programs, and combined with scientific dietary guidance and enteral nutrition support, the nutritional status of patients was significantly improved. Wang et al [20] revealed that highquality nursing for colorectal carcinoma patients undergoing laparoscopic examination can effectively reduce the incidence of postoperative complications, relieve the pain, and improve the gastrointestinal function of patients. In addition, the pain evaluation herein found no significant difference between the two groups before and after nursing, but significantly better alleviation of pain in the RG than that in the CG, which indicated that rapid rehabilitation could significantly reduce the postoperative pain of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current clinical care content for ASBO is still lacking in specificity, and for the treatment of more complex transnasally inserted intestinal obstruction catheters, traditional nursing strategies are obviously not enough [ 9 ]. At present, many authors have pointed out that a targeted nursing strategy for ASBO and transnasally inserted intestinal obstruction catheters needs to be found as soon as possible in the clinic, but no significant results have been achieved so far [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%